Pro-Vaccination Flu and COVID-19 Messages: Evidence of Congenial Targeted and Spillover Effects - James Price Dillard; Lijiang Shen (COVID, 2024)
Given the plentitude of messages in the public arena that promote vaccination against different diseases or raise the possibility of vaccine mandates, we asked whether message effects in one disease domain might spill over into other domains. Our experiment exposed individuals (N = 1755) recruited from an opt-in online panel (Qualtrics) on influenza or COVID-19 pro-vaccination messages then measured intentions to vaccinate for each disease and intentions to support a vaccine mandate for each disease. Messages that targeted flu (vs. COVID-19) exhibited stronger effects on intentions to vaccinate for corresponding (vs. noncorresponding) disease. We observed positive spillover from intention to vaccinate against one disease to intention to vaccinate against the other disease, as well as from vaccination intention type to support for corresponding and noncorresponding vaccine mandates. Although pro-vaccination flu and COVID-19 messages have multiple effects, those effects are congenial. The results adjudicate differences in spillover theory and suggest synergistic effects between pro-vaccination campaigns.